Intergenerational transmission of family and communication social capital in Pakistan: an empirical analysis. (25th August 2021) - Azid, Toseef; Shareef, Fareed; Kayani, Zafar
Using a sample of 613 households of district Multan a district of Pakistan, this study investigates the transmission of family and communication social capital across generations. Models of social capital transmission with core variables support the hypothesis that parental social networks determine their offsprings' social capital. For general analysis, the majority of control variables relating to the socio-demographic status have remained insignificant. The study explores that the transmission of family and communication social capital from parents to their children is specific in nature, not like a hereditary process. It means that children seem to acquire particular forms of social capital from their parents, rather than experiencing any collective social capital improvement due to their parents' practices.